A MODEL OF AN ENHANCED COMPUTER GAME SERVER IN MULTIPLAYER ENVIRONMENTS (Computer systems and information technologies, 2024)
The rapid evolution of multiplayer gaming has led to increasingly complex virtual environments that require precise synchronous movement mechanics to be competitive. One of the main challenges of interacting with large numbers of users in real-time in a multiplayer environment is the effect of network delays on character movements. In addition to the constant component, network delays have a variable component that is random and at the same time can be different on different network segments when the server interacts with different clients. The article examines the operation of a computer game server and proposes a model of advanced character movement control for multiplayer environments that provides smooth transitions between animation states through the concept of client-side prediction. The model is based on the state transition diagram of the server and describes its operation during a multiplayer game. To analyze the processes implemented by the server, we defined its five states: listening state, packet delay check state, mobility check state, client data update state, and preauthorization data update state. The object of modeling is a random process characterized by discrete states and continuous time, the model of which is presented as a system of differential equations. The results of solving this system of equations are analytical expressions for estimating the probabilities of a computer game server being in each of the possible states depending on the intensity of transitions between states. The presented mathematical apparatus describes the influence of incoming requests of different intensities on maintaining the necessary quality of system operation. The resulting formulas can be used for further analysis of the server's operation in various scenarios. Based on them, recommendations for improving data exchange algorithms in the system can be developed.
Keywords: multiplayer game development; multiplayer server management; character movement; telecommunication network; model